Quality Of the Work Environment Through the Approach of Employee Perceptions in Indonesian Manufacturing Companies - Silvia Listia Fadillah; Putri Fatikasari; Ikva Diana Yesta; Farah Fadillah Amru; Lisa Harry Sulistiyowati; Jay miguel (PT. BATARI EDU CALYA, 2024)
This study aims to examine the relationship between employees’ perceptions of the quality of the work environment, employee behavior, and organizational functioning within an Indonesian manufacturing company. A quantitative research design was employed using a survey method. Data were collected through structured questionnaires distributed to employees across various departments. The variables examined include perceived quality of the work environment, employee work behavior, and organizational effectiveness. The findings reveal a positive and significant correlation between employees’ perceptions of work environment quality and their work behavior. Employees who perceive their work environment as supportive, safe, and conducive tend to demonstrate more constructive behaviors, higher engagement, and stronger organizational commitment. The study contributes to the existing body of knowledge by empirically demonstrating how perceived workplace quality influences behavioral outcomes and organizational performance. The results suggest that organizations should continuously enhance both the physical and psychosocial dimensions of the workplace to foster employee satisfaction and productivity. A comprehensive understanding of how individual perceptions shape behavior and contribute to organizational outcomes is essential for achieving sustainable competitive advantage in an increasingly globalized market.